AoStuA, an APSES transcription factor, regulates the conidiation, trap formation, stress resistance and pathogenicity of the nematode‐trapping fungus Arthrobotrys oligospora. (8th September 2019) - Xie, Meihua; Wang, Yunchuan; Tang, Liyan; Yang, Le; Zhou, Duanxu; Li, Qing; Niu, Xuemei; Zhang, Ke‐Qin; Yang, Jinkui
Summary: The APSES protein family comprises a conserved class of fungus‐specific transcriptional regulators. Some members have been identified in partial ascomycetes. In this study, the APSES protein StuA (AoStuA) of the nematode‐trapping fungus Arthrobotrys oligospora was characterized. Compared with the wild‐type (WT) strain, three Δ AoStuA mutants grew relatively slowly, displayed a 96% reduction in sporulation capacity and a delay in conidial germination. The reduced sporulation capacity correlated with transcriptional repression of several sporulation‐related genes. The mutants were also more sensitive to chemical stressors than the WT strain. Importantly, the mutants were unable to produce mycelial traps for nematode predation. Moreover, peroxisomes and Woronin bod ies were abundant in the WT cells but hardly found in the cells of those mutants. The lack of such organelles correlated with transcriptional repression of some genes involved in the biogenesis of peroxisomes and Woronin bod ies. The transcript levels of several genes involved in the cAMP/PKA signalling pathway were also significantly reduced in the mutants versus the WT strain, implicating a regulatory role of AoStuA in the transcription of genes involved in the cAMP/PKA signalling pathway that regulates an array of cellular processes and events. In particular, AoStuA is indispensable for A . oligospora trap formation and virulence.